ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TANDAN BUAH SEGAR (TBS) DENGAN METODE SIMULASI MONTE CARLO - Cindy Artika; Sajaratud Dur; Ismail Husein (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The development of palm oil production is quite rapid in Indonesia. The method used to estimate inventory costs in this study is the Monte Carlo Simulation method. Monte Carlo simulation is used in structuring optimal raw material policies. The purpose of this research is to predict and optimize raw material inventory costs for the future. The results of the total cost of raw material inventory by Monte Carlo Simulation Calculations are smaller than the total cost of inventory by company calculations. The total cost of preparation using Monte Carlo Simulation Calculations is Rp. 16,873,743,694. Meanwhile, the total calculation preparation costs obtained by the company amounted to Rp. 17,207,020,022, and savings of Rp. 333,276,328